Post-COVID-19 fatigue: A systematic review - Joli, Jian; Buck, Patrizia; Zipfel, Stephan; Stengel, Andreas (Frontiers in Psychiatry, 2022)
Fatigue is recognized as one of the most commonly presented long-term complaints in individuals previously infected with SARS-CoV-2. This systematic review was performed to describe symptoms, etiology, possible risk factors related to post-COVID-19 fatigue and the therapeutic approaches used for the treatment of post-COVID-19 fatigue. For the systematic literature search the databases PubMed, Web of Science, Cochrane Library, and PsycInfo were used. All articles that met the inclusion criteria were analyzed for demographics, clinical data and treatment. Included were studies which focused on an adult population (18-65 years old); elderly patients and patients with chronic somatic diseases which can also cause fatigue were excluded. We identified 2851, screened 2193 and finally included 20 studies with moderate to high methodological quality, encompassing 5629 participants. Potential risk factors for post-COVID-19 fatigue were old age, female sex, severe clinical status in the acute phase of infection, a high number of comorbidities, and a prediagnosis of depression/anxiety. Lastly, a possible autoimmune etiology was suspected. Several treatment approaches have been tested mostly in small and uncontrolled studies so far: A Chinese herbal formulation improved breathlessness and fatigue. Moreover, molecular hydrogen (H2) inhalation had beneficial health effects in terms of improved physical (6-min walking test) and respiratory function in patients with post-COVID-19. Patients also noticed improvement in fatigue after undergoing hyperbaric oxygen therapy (HBOT) and enhanced external counterpulsation (EECP). Lastly. muscle strength and physical function were improved after undergoing an 8-week biweekly physical therapy course including aerobic training, strengthening exercises, diaphragmatic breathing techniques, and mindfulness training. However, larger and controlled studies e.g. investigating the effect of physical and / or psychotherapy for patients with post-COVID-19 fatigue are urgently warranted.